2019
DOI: 10.1093/eurpub/ckz185.125
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and renal cell cancer risk in Chinese males: a population-based prospective study

Abstract: Background Metabolic syndrome (MetS) is now a common public health problem. Few researches have reported the relationship between MetS and the risk of renal cell cancer (RCC). To investigate the association of metabolic syndrome and its components with the risk of RCC in Chinese males, the study was performed in the Kailuan male cohort, a large prospective cohort study. Methods A total of 104,333 eligible males enrolled in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…listed in Figure 1. Finally, eight observational studies were identified and included in the meta-analysis (23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…listed in Figure 1. Finally, eight observational studies were identified and included in the meta-analysis (23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Methodsmentioning
confidence: 99%
“…These studies were performed in Italy, the Netherlands, Norway, Austria, Sweden, Spain, Korea, and China, and designed as prospective cohorts (23)(24)(25)28), retrospective cohorts (26,27,29), and the matched case-control study (30). Six of them included adult participants in community settings (23,24,(26)(27)(28)30), while the other two included adult patients with vascular diseases (25) and adults with hepatitis B virus infection (29). The sample sizes of the included studies varied between 6,172 and 7,613,865.…”
Section: Summary Of Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations